An inducible gene from glycoside hydrolase one family of Plutella xylostella decreases larval survival when feeding on host plant - Chen, Wei; Dong, Yuhong; Zheng, Ling; Lai, Yingfang; Li, Feifei; Zhou, Li; Wang, Beibei; You, Minsheng; He, Weiyi (Frontiers in Physiology, 2022)
Glycoside hydrolase family 1 (GH1) members exhibit a broad substrate spectrum and play important roles in insect-plant interactions, such as the defensive β-glucosidase and β-thioglucosidase (so-called myrosinase). However, knowledge about the expression profiling and function of glycoside hydrolase family 1 members in a specialist pest of crucifers Plutella xylostella is still limited. In this study, 13 putative glycoside hydrolase family 1 members of P. xylostella were identified based on the sequence characteristics, while no myrosinase activity was detectable in P. xylostella using gas chromatography-mass spectrometry (GC-MS). Expression profiling of these glycoside hydrolase family 1 members identified the midgut-specific gene Px008848 that is induced by host plant. Further experiments revealed that the in vitro expressed Px008848 protein had β-glucosidase activity and the survival rate of the larvae feeding on wounded Arabidopsis thaliana leaves declined when leaves were treated with purified Px008848 protein. When CRISPR/Cas9-based homozygous mutant larvae of Px008848 and wild-type larvae were respectively transferred onto the A. thaliana, the larval survival rate of the mutant larvae was significantly higher than that of the wild-type individuals. Our work showed that certain insect glycoside hydrolase family 1 gene may have negative effect on the development of larvae feeding on the host plant, which broadened our understandings on the evolutionary function of this gene family in the insect-plant interaction.